Reports on industrial information technology. Vol. 12 - Puente León, FernandoDostert, Klaus [Hrsg.] (Reports on industrial information technology / Fernando Puente León, Klaus Dostert (eds.); Institute of Industrial Information Technology, Karlsruhe Institute of Technology, 2010)
The 12th volume of Reports on Industrial Information Technology presents some selected results of research achieved at the Institute of Industrial Information Technology during the last two years.These results have contributed to many cooperative projects with partners from academia and industry and cover current research interests including signal and image processing, pattern recognition, distributed systems, powerline communications, automotive applications, and robotics.